Speaking for animals : animal autobiographical writing - DeMello, Margo; DeMello, Margo (Routledge advances in sociology, 2013)
For thousands of years, in the myths and folktales of people around the world, animals have spoken in human tongues. Western and non-Western literary and folkloric traditions are filled with both speaking animals, some of whom even narrate or write their own autobiographies. Animals speak, famously, in children’s stories and in cartoons and films, and today, social networking sites and blogs are both sites in which animals—primarily pets—write about their daily lives and interests. Speaking for Animals is a compilation of chapters written from a variety of disciplines that attempts to get a handle on this cross cultural and longstanding tradition of animal speaking and writing. It looks at speaking animals in literature, religious texts, poetry, social networking sites, comic books, and in animal welfare materials and even library catalogs, and addresses not just the "whys" of speaking animals, but the implications, for the animals and for ourselves.